How Elastic are Bands Those are Used in Everyday Life? - Sharma, Om; Sharma, Dipti (European Journal of Applied Sciences, 2021)
Elastic materials are found all around us and knowing at least a general overview on how they behave is useful and important. The purpose for this research work is to understand what Physics is behind rubber bands and how it is connected with the dimension of rubber bands (length, width, thickness and area) and its stiffness (spring constant and Young’s modulus). To test this, a handmade wooden stand by student author was used with a ruler attached to it. Then various types of rubber bands were hung and their increase in length was measured by increasing weight on it each time. The obtained data of dimensions of the bands and increase in length was compared to Hooke’s Law and Young’s modulus to understand stiffness of the bands. A higher spring constant represents that the material is stiffer and requires more force to stretch it whereas higher Young’s modulus shows the stability of the material. This research is a project work done by a high school student to present in MA science fair in USA and project won an honorable award at regional level and went to the state level in USA in 2021.